Antigen Specific Humoral and Cellular Immunity Following SARS-CoV-2 Vaccination in ANCA-Associated Vasculitis Patients Receiving B-Cell Depleting Therapy - Marty, Paige K.; Van Keulen, Virginia P.; Erskine, Courtney L.; Shah, Maleeha; Hummel, Amber; Stachowitz, Michael; Fatis, Samantha; Granger, Dane; Block, Matthew S.; Duarte-García, Alí; Warrington, Kenneth J.; Theel, Elitza S.; et al. (Frontiers in Immunology, 2022)
Humoral vaccine responses are known to be suboptimal in patients receiving B-cell targeted therapy, and little is known about vaccine induced T-cell immunity in these patients. In this study, we characterized humoral and cellular antigen-specific anti-SARS-CoV2 responses following COVID-19 vaccination in patients with ANCA-associated vasculitis (AAV) receiving anti-CD20 therapy, who were either B-cell depleted or B-cell recovered at the time of vaccination and in normal control subjects. SARS-CoV-2 anti-spike (S) and anti-nucleocapsid (NC) antibodies were measured using electrochemiluminescence immunoassays, while SARS-CoV-2 specific T-cell responses to S glycoprotein subunits 1 (S1) and 2 (S2) and receptor biding domain peptide pools using interferon-gamma enzyme-linked immunosorbent spot (ELISPOT) assays. In total, 26 recently vaccinated subjects were studied. Despite the lack of a measurable humoral immune response, B-cell depleted patients mounted a similar vaccine induced antigen-specific T-cell response compared to B-cell recovered patients and normal controls. Our data indicate that to assure a humoral response in patients receiving anti-CD20 therapy, SARS-CoV-2 vaccination should ideally be delayed until B-cell recovery (CD-20 positive B-cells > 10/ul). Nevertheless, SARS-CoV-2 vaccination elicits robust, potentially protective cellular immune responses in these subjects. Further research to characterize the durability and protective effect of vaccine-induced anti-SARS-CoV-2 specific T-cell immunity are needed.